Zmienność szyszek jodły pospolitej (Abies alba Mill.) – zmienność parametrów zewnętrznych szyszek - Aniszewska, Monika; Błuszkowska, Urszula (Leśne Prace Badawcze, 2016)
This study aimed at determining the shape of closed silver fir cones from the Jawor Forest District (Wroclaw), based purely on measurements of their length and thickness. Using these two parameters, the most accurate estimations were achieved with a fourth-degree polynomial fitting function. We then calculated the cones’ surface area and volume in three different ways: 1) Using the fourth-degree polynomial shape estimation, 2) Introducing indicators of compliance (k1, k2, k3) to calculate the volume and then comparing it to its actual value as measured in a pitcher filled with water, 3) Comparing the surface area of the cones as calculated with the polynomial function to the value obtained from ratios of indicators of compliance (ratios k4 and k5).We found that the calculated surface area and volume were substantially higher than the corresponding measured values. Test values of cone volume and surface area as calculated by our model were 8% and 5% lower, respectively, compared to direct measurements. We also determined the fir cones apparent density to be 0.8 g·cm -3 on average. The gathered data on cone surface area, volume and bulk density is a valuable tool for optimizing the thermal peeling process in mill cabinets to acquire high quality seeds.